2015
DOI: 10.5530/jyp.2015.4.7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of medication adherence and knowledge regarding the disease among ambulatory patients with diabetes mellitus in Karachi, Pakistan

Abstract: Objective: To report medication adherence among ambulatory patients with diabetes mellitus (DM) using Morisky 8-item medication adherence MMAS-8 scale and assess current standard of knowledge regarding their disease using a especially developed Patient 10-item Knowledge Assessment PKA-X scale. Methods: A quantitative cross sectional study was conducted for 3 months in Karachi, Pakistan using Morisky 8-item medication adherence scale ® documenting the medication adherence of ambulatory patients with DM and to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
0
6
1
1
Order By: Relevance
“…Most students were Saudi, aged between 18-20 y and were studying Pharm. D. Several studies have reported similar enrolment in other colleges of Saudi Arabia [17,18]. The majority of students indicated that diabetes mellitus is prevalent in their family.…”
Section: Discussionmentioning
confidence: 72%
“…Most students were Saudi, aged between 18-20 y and were studying Pharm. D. Several studies have reported similar enrolment in other colleges of Saudi Arabia [17,18]. The majority of students indicated that diabetes mellitus is prevalent in their family.…”
Section: Discussionmentioning
confidence: 72%
“…This is encouraging as previous studies conducted in other parts of Pakistan reported poor medication adherence among diabetes patients. [19][20][21] Poor medication adherence has also been observed among diabetes patients in the South Asian region. [26][27][28] One possible reason for the differences seen between the various studies is the different methodologies used to assess medication adherence.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] However to date, medication adherence has not been seen as a major concern among health care providers in Pakistan. [19] This may be because little information is currently available regarding adherence rates among these patients, although what information is available suggests poor medication adherence in practice. [20][21][22] We would like to add to this knowledge by looking specifically at potential key predictors of medication adherence as a starting point for developing future initiatives in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…Economic status influences someone to conduct self-care management. State that the high cost of treatment in type 2 Diabetes Mellitus patients is still an important reason in terms of preventing suboptimal levels of adherence 16 .…”
Section: Income Factormentioning
confidence: 99%